Drying of red ginger slices using tray dryer integrated with pyrolysis reactor as a heat source: Evaluation on the drying characteristics, red ginger quality, and drying kinetics - Hasibuan, Rosdanell; Haryanto, Bode; Aainaa Izyan, Nafsun; Pramananda, Viqry; Siregar, Fatimah Fahira; Fazillah, Risma (Elsevier Ltd, 2025)
Red ginger is one of the medicinal plants that contain gingerol and shogaol. Drying is the post-harvest processing of red ginger, but it requires serious attention. This study evaluated the performance of tray dryer intregated with a pyrolysis reactor in red ginger drying. The best dried red ginger was obtained at 70 °C and a thickness of 0.5 cm, with a moisture content of 9.71 % and two-period drying characteristics. Investigation using SEM-EDS, FTIR, and GC-MS were employed to characterize the red ginger before and after drying. Drying kinetic modelling revealed the Page model as the most suitable model.